1988
DOI: 10.1037/0022-3514.55.5.758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exposure to violent and sexually degrading depictions of women.

Abstract: In this study we investigated the effects of emotional desensitization to films of violence against women and the effects of sexually degrading explicit and nonexplicit films on beliefs about rape and the sexual objectification of women. Male subjects viewed either two or five R-rated violent "slasher," X-rated nonviolent "pornographic," or R-rated nonviolent teenage-oriented ("teen sex") films. Affective reactions and cognitive perceptions were measured after each exposure. Later, these men and no-exposure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
2
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 36 publications
10
141
2
3
Order By: Relevance
“…Similarly, Malamuth and Check (1981) found an increased acceptance of physical aggression toward women by college men several days after they had watched violent sex scenes. Linz (1988) and colleagues report similar findings of desensitization to violent 'slasher' films.…”
Section: Experiments On Emotional Desensitizationsupporting
confidence: 63%
“…Similarly, Malamuth and Check (1981) found an increased acceptance of physical aggression toward women by college men several days after they had watched violent sex scenes. Linz (1988) and colleagues report similar findings of desensitization to violent 'slasher' films.…”
Section: Experiments On Emotional Desensitizationsupporting
confidence: 63%
“…People high on rape myth acceptance frequently fail to acknowledge that descriptions fitting the legal definition of rape are in fact examples of rape (e.g., Fischer, 1986;Norris & Cubbins, 1992). Furthermore, studies have generally found that people high (vs. low) on rape myth acceptance assign less responsibility and blame to perpetrators (Check & Malamuth, 1985;Quackenbush, 1989), and more responsibility and blame to victims of rape (e.g., Blumberg & Lester, 1991;Check & Malamuth, 1985;Jenkins & Dambrot, 1987;Linz, Donnerstein, & Adams, 1989;Linz, Donnerstein, & Penrod, 1988;Muehlenhard & MacNaughton, 1988). In short, rape myth acceptance is a reliable predictor of various reactions to rape incidents.…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…3,56 Titillating violence in sexual contexts and comic violence are particularly dangerous, because they associate positive feelings with hurting others. 57,58 One study of nearly 32 000 teenagers in 8 different countries, for example, revealed that heavy television-viewing was associated with bullying. 59 In addition to modeling violent behavior, entertainment media inflate the prevalence of violence in the world, cultivating in viewers the "meanworld" syndrome, a perception of the world as a dangerous place.…”
Section: Impactmentioning
confidence: 99%